The correlation of industrial work experience and soft skills on work readiness of graduated of vocational high school - Azizah, Diana Nur; Muslim, Supari; Cholik, Mochamad (International Journal for Educational and Vocational Studies, 2021)
The demands of the world of work require that every student must have competence. Work readiness to enter the world of work can be influenced by several factors. Do soft skills and industrial practical work experience affect vocational students' work readiness? This study aims to obtain a correlation between practical industrial work experience and soft skills on vocational school students' work readiness with quantitative methods through a questionnaire using google form at Vocational High School of RadenPatah, Mojokerto, class XII, majoring in Mechanical Engineering. The data obtained from 72 students in the sample were analyzed by using the Multiple Regression Test using SPSS 23 software. The results of this study indicate: (1) there is a significant correlation with the direction of a positive relationship between industrial work practice experience and work readiness of 24.4% (2) there is a significant correlation with the direction of the positive relationship between soft skills and work readiness of 25.4% (3) there is a significant correlation with the direction of the positive relationship between industrial work practice experience and soft skills simultaneously to work readiness by 31.1%.